Review of Temporary Crating of Farrowing and Lactating Sows - Goumon, Sébastien; Illmann, Gudrun; Moustsen, Vivi A.; Baxter, Emma M.; Edwards, Sandra A. (Frontiers in Veterinary Science, 2022)
Temporary crating (TC) provides lactating sows with the opportunity to move more freely after crate opening a few days after parturition. The aim of this paper was to evaluate whether TC gives overall welfare improvement when compared to permanent crating or free farrowing. This review shows that when pens with TC allow the sows to turn during the majority of time in the farrowing unit, it is the pen design and period of confinement in a crate within it that influence how different functional and motivated behaviours can be fulfilled. This review indicates that there are at least short-term benefits to sows when confinement is reduced, as shown by reported increased exploration and interactions with piglets when not permanently crated. It remains unclear whether there are any longer-term beneficial effects (until or beyond weaning) due to the paucity of studies. It is uncertain whether the observed short-term benefits translate to other welfare indicators. Research findings indicate no reduction in the frequency of stereotypies or body lesions and do not provide a clear answer regarding sow stress response when released from confinement. Compared to free farrowing, TC appears beneficial for reducing piglet mortality. The impact of the time of onset of TC on the farrowing process and piglet mortality have been inconsistent. While confinement before farrowing prevents nest building behaviour, consequences of this for sow physiology have been ambiguous. Confining the sow briefly after farrowing may be the best compromise, allowing the sow to perform motivated nest-building behaviour, but the risks of crushing during the unconfined farrowing period may increase. Subsequent crate reopening seems to increase piglet mortality but only if done earlier than 3-5 days after farrowing. The review provides methodological considerations, a proposal for consistent and accurate terminology when describing systems and highlights gaps of knowledge. In conclusion, TC is a step forward to better pig welfare compared to the farrowing crate as it allows some freedom of movement for sows without impairing piglet welfare. However, more comprehensive research is needed to draw sound conclusions as to whether TC is a viable transition from permanent crating to free farrowing.